CYTOKININ-RESPONSIVE GROWTH REGULATOR regulates cell expansion and cytokinin-mediated cell cycle progression. Issue 3 (28th April 2021) - Park, Joonghyuk; Lee, Seungchul; Park, Geuntae; Cho, Hyunwoo; Choi, Daeseok; Umeda, Masaaki; Choi, Yeonhee; Hwang, Daehee; Hwang, Ildoo
Abstract: The cytokinin (CK) phytohormones have long been known to activate cell proliferation in plants. However, how CKs regulate cell division and cell expansion remains unclear. Here, we reveal that a basic helix–loop–helix transcription factor, C YTOK ININ-RESPONSIVE G ROWTH REGULATOR (CKG), mediates CK-dependent regulation of cell expansion and cell cycle progression in Arabidopsis thaliana . The overexpression of CKG increased cell size in a ploidy-independent manner and promoted entry into the S phase of the cell cycle, especially at the seedling stage. Furthermore, CKG enhanced organ growth in a pleiotropic fashion, from embryogenesis to reproductive stages, particularly of cotyledons. In contrast, ckg loss-of-function mutants exhibited smaller cotyledons. CKG mainly regulates the expression of genes involved in the regulation of the cell cycle including WEE1 . We propose that CKG provides a regulatory module that connects cell cycle progression and organ growth to CK responses. Abstract : Cytokinin-responsive transcription factor controls cell cycle and cell expansion, leading to organ growth in Arabidopsis.